Pengembangan Manajemen Sumber Daya Manusia Terhadap Peningkatkan Mutu Pendidikan - Waya; Haratua, Chandra Sagul (PT. Lancar Media Komunikasi, 2024)
This study aims to find out how important human resource management is in improving the quality of education in an institution. This study uses the library research method, where the discussion of this research is based on expert opinion and the results of previous research. Research techniques with data analysis in the form of content analysis (content analysis) to select data and information contained in the various library materials studied. The results of this study note that the increase in the quality of education in an institution is due to the role of human resource management so that solutions are found to deal with challenges that arise in improving the quality of education in an institution so that it can make a clear contribution to educational goals.